2019
DOI: 10.1016/j.jpain.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A Definition of “Flare” in Low Back Pain: A Multiphase Process Involving Perspectives of Individuals With Low Back Pain and Expert Consensus

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Although the reference to the impact on activity in the definition of flare might influence the participants' decision, this was an intentional decision based on the consensus opinions of experts and individuals with LBP. 5 This definition is aligned with the key note regarding the recently updated definition of pain that states "Pain is always a personal experience that is influenced to varying degrees by biological, psychological, and social factors." 23…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the reference to the impact on activity in the definition of flare might influence the participants' decision, this was an intentional decision based on the consensus opinions of experts and individuals with LBP. 5 This definition is aligned with the key note regarding the recently updated definition of pain that states "Pain is always a personal experience that is influenced to varying degrees by biological, psychological, and social factors." 23…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
“…A small case-crossover study identified that stress, depressive symptoms, and prolonged sitting, but not engagement in physical activity, were associated with LBP flares defined by an increased in pain. 44 In a more recent study, participants reported pain (several times per day) and whether they had experienced a flare (self-reported flare [SRF]; according to a standardised definition that considered multiple domains 5,7 ). This study identified that the risk of a 2-point increase in pain was increased by higher pain levels in the previous afternoon and evening, fatigue, fear avoidance, engaging in physical activity, and very poor sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were eligible to take part if they had sought care for LBP in the preceding 6 months and if they had experienced at least 2 episodes or flare-ups of LBP in the past 2 years. An episode was defined as “pain that lasts more than 24 hours, with at least a week of recovery (0 or 1 on a 10-point scale where 0 is no pain and 10 is pain as bad as it could be) 33 in between episodes.” 1 A flare-up was defined as “a worsening of your condition that lasts from hours to weeks that is difficult to tolerate and generally impacts your usual activities and/or emotions.” 9 Other inclusion criteria were age older than 18 years, ability to speak, read, and understand English, and currently living in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Back pain has also been described by its intensity, frequency, influence on activity and duration (9). However, the accepted duration classificationacute 0-3 weeks, subacute 4-12 weeks, and chronic pain >12 weeks (10)has recently been challenged, following findings that back pain fluctuates over time with symptoms on and off for years (11,12). Up to 90% of all LBP cases can be categorised as non-specific, where the underlying pathology or disease cannot be identified through diagnostic assessment (13).…”
Section: Low Back Painmentioning
confidence: 99%
“…The advantages of maximum likelihood imputation are: 1) it results in unbiased estimates and provides more validity than ad-hoc approaches to missing data; and 2) it uses all available data and therefore preserves sample size and statistical power (170). It is well known that disability and pain fluctuate over time in LBP (11,12), therefore imputed data might not reflect this variation. However this is likely to be similar in both groups.…”
Section: Strengths and Limitationsmentioning
confidence: 99%